An empirical investigation into the effectiveness of genetic genealogy to identify individuals in the UK. (May 2020) - Thomson, Jim; Clayton, Tim; Cleary, John; Gleeson, Maurice; Kennett, Debbie; Leonard, Michelle; Rutherford, Donna
Highlights: Ten volunteer UK residents provided high density SNP data downloaded from a direct-to-consumer testing company. Data were uploaded anonymously to GEDmatch and genetic genealogy methods used to attempt to identify the volunteers by name. Four out of a sample of ten UK residents were identified by name or as one of a group of named siblings. Demonstration that genetic genealogy techniques can be effective in investigation of individual identity for cases in the UK. Abstract: The use of genetic genealogy techniques to identify Joseph James DeAngelo as the prime suspect in the Golden State Killer case in 2018 has opened up a new approach to investigation of cold cases. Since that breakthrough, genetic genealogy methods have been reported to be applied to around 100 cases. To date, all of these reports relate to investigations in the US, where the high uptake of "direct-to-consumer" (DTC) genetic testing by individuals conducting private ancestral research has provided the necessary publicly available data for successful forensic investigations. We have conducted a study to assess the likely effectiveness of genetic genealogy techniques if applied to investigations in the UK. Ten volunteers provided their own SNP array data, downloaded from a DTC provider of their choice. These data sets were anonymised and uploaded to the GEDmatch Genesis genealogy website, mimicking data sets from unsourced crime samples or unidentified human remains. A team of experienced genealogists then attempted to identify the donors of the anonymised data sets by working with matches on the database and identifying points where the matches' trees intersect to determine their shared family lineages which were further investigated using traditional resources (such as birth, marriage, death and census records, social media and online family trees). Through these methods, four of the ten donors were identified, at least to the level of one of a set of siblings. This confirms that, despite the over-representation of US citizens on publicly accessible genealogy databases, there is still potential for effective use in investigations outside the US where legislation permits. One of our four identified individuals was of Indian heritage (via St Vincent and the Grenadines) highlighting that in the right circumstances individuals of non-European origin can be identified.